ALTERED DEFAULT MODE NETWORK (DMN) RESTING STATE FUNCTIONAL CONNECTIVITY FOLLOWING A MINDFULNESS‐BASED EXPOSURE THERAPY FOR POSTTRAUMATIC STRESS DISORDER (PTSD) IN COMBAT VETERANS OF AFGHANISTAN AND IRAQ. Issue 4 (1st April 2016) - King, Anthony P.; Block, Stefanie R.; Sripada, Rebecca K.; Rauch, Sheila; Giardino, Nicholas; Favorite, Todd; Angstadt, Michael; Kessler, Daniel; Welsh, Robert; Liberzon, Israel
Abstract : Background: Recent studies suggest that mindfulness may be an effective component for posttraumatic stress disorder (PTSD) treatment. Mindfulness involves practice in volitional shifting of attention from "mind wandering" to present‐moment attention to sensations, and cultivating acceptance. We examined potential neural correlates of mindfulness training using a novel group therapy (mindfulness‐based exposure therapy (MBET)) in combat veterans with PTSD deployed to Afghanistan (OEF) and/or Iraq (OIF). Methods: Twenty‐three male OEF/OIF combat veterans with PTSD were treated with a mindfulness‐based intervention ( N = 14) or an active control group therapy (present‐centered group therapy (PCGT), N = 9). Pre‐post therapy functional magnetic resonance imaging (fMRI, 3 T) examined resting‐state functional connectivity (rsFC) in default mode network (DMN) using posterior cingulate cortex (PCC) and ventral medial prefrontal cortex (vmPFC) seeds, and salience network (SN) with anatomical amygdala seeds. PTSD symptoms were assessed at pre‐ and posttherapy with Clinician Administered PTSD Scale (CAPS). Results: Patients treated with MBET had reduced PTSD symptoms (effect size d = 0.92) but effect was not significantly different from PCGT ( d = 0.46). Increased DMN rsFC (PCC seed) with dorsolateral dorsolateral prefrontal cortex (DLPFC) regions and dorsal anterior cingulate cortex (ACC) regions associated with executive control was seen following MBET. A group × time interaction found MBET showed increased connectivity with DLPFC and dorsal ACC following therapy; PCC–DLPFC connectivity was correlated with improvement in PTSD avoidant and hyperarousal symptoms. Conclusions: Increased connectivity between DMN and executive control regions following mindfulness training could underlie increased capacity for volitional shifting of attention. The increased PCC–DLPFC rsFC following MBET was related to PTSD symptom improvement, pointing to a potential therapeutic mechanism of mindfulness‐based therapies.